Transformasi Minat Belajar Melalui Gamifikasi: Studi Kasus di SMA Negeri 4 Tanjungpinang: (Transforming Learning Interest Through Gamification: A Case Study at Tanjungpinang State Senior High School 4) - Fathiha, Fauza Sandra Nurul; Hubin, Helena Petryana; Putri, Helmi; Lestari, Indri Eka; Yunika, Risma (BIODIK, 2025)
This study aims to describe students' learning interests and learning outcomes in relation to the application of game-based learning integrated with the Discovery Learning model at SMAN 4 Tanjungpinang. The research used Classroom Action Research (CAR) with research subjects including students from classes X.3, X.6, XI.1.1, XI.1.2, and XI.1.3. Data collection was carried out through a student learning interest questionnaire using a Likert scale supported by a learning activity observation sheet. The data obtained was analyzed by converting the scores into percentages. The results showed that game-based learning had a positive effect on students' interest and learning activities. Students showed high enthusiasm, active involvement in learning, and positive perceptions of their understanding of the material. The integration of game-based learning with the Discovery Learning model was able to create an interactive, enjoyable, and student-centered learning atmosphere. Thus, game-based learning can be used as an alternative learning strategy to increase students' interest in learning Biology. Abstrak. Penelitian ini bertujuan untuk mendeskripsikan minat belajar dan hasil belajar siswa terhadap penerapan pembelajaran berbasis games yang diintegrasikan dengan model Discovery Learning di SMAN 4 Tanjungpinang. Penelitian menggunakan Penelitian Tindakan Kelas (PTK) dengan subjek penelitian meliputi siswa kelas X.3, X.6, XI.1.1, XI.1.2, dan XI.1.3. Pengumpulan data dilakukan melalui angket minat belajar siswa menggunakan skala Likert yang didukung oleh lembar observasi aktivitas belajar. Data yang diperoleh dianalisis dengan mengonversi skor ke dalam bentuk persentase. Hasil penelitian menunjukkan bahwa pembelajaran berbasis games memberikan pengaruh positif terhadap minat dan aktivitas belajar siswa. Siswa menunjukkan antusiasme yang tinggi, keterlibatan aktif dalam pembelajaran, serta persepsi yang positif terhadap pemahaman materi. Integrasi pembelajaran berbasis games dengan model Discovery Learning mampu menciptakan suasana belajar yang interaktif, menyenangkan, dan berpusat pada siswa. Dengan demikian, pembelajaran berbasis games dapat dijadikan sebagai alternatif strategi pembelajaran untuk meningkatkan minat belajar siswa pada mata pelajaran Biologi.